1977
DOI: 10.1002/dev.420100205
|View full text |Cite
|
Sign up to set email alerts
|

A critical period for social isolation in the rat

Abstract: Rats housed in social isolation show heightened levels of object-contact in an open-field and are slower than socially-housed controls to emerge from a small enclosure into an unfamiliar environment. Isolation between 25 and 45 days of age produced an irreversible effect upon object contact but had no lasting effect if between 16 and 25 days or after 45 days. In contrast to object contact, emergence was affected by isolation at any age and the effect was reversed by subsequent social housing. Thus the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
142
0
3

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(155 citation statements)
references
References 8 publications
(13 reference statements)
10
142
0
3
Order By: Relevance
“…This could indicate a delayed habituation of 1-animals to novel environments. Einon and Morgan [7] claimed a slower habituation to contacts with objects in the open field of isolated animals, but File [10] reported that a general impairment in the ability to habituate is not a characteristic of isolates. However, differences in habituation to the testeage in individually and group-housed animals have been described in mice [ 1,15].…”
Section: Fig 3 Correlation Diagram Comparing Frequency and Durationmentioning
confidence: 99%
“…This could indicate a delayed habituation of 1-animals to novel environments. Einon and Morgan [7] claimed a slower habituation to contacts with objects in the open field of isolated animals, but File [10] reported that a general impairment in the ability to habituate is not a characteristic of isolates. However, differences in habituation to the testeage in individually and group-housed animals have been described in mice [ 1,15].…”
Section: Fig 3 Correlation Diagram Comparing Frequency and Durationmentioning
confidence: 99%
“…Exposure to stressors during juvenility was reported to produce more pronounced effects than exposure at earlier or later ages, affecting object exploration in adulthood (Einon and Morgan, 1977), fluid intake (McGivern et al, 1996), and adulthood social and nonsocial behaviors associated with disregulation of endogenous opioid system development ( Van den Berg et al, 1999a, b, c, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…After long-term impoverished housing rats develop an array of behavioural changes, including, amongst others, increased aggression [ 14,26], high locomotor activity [112] and altered social behaviour [ 17]. Several authors have contributed the impoverishment effect to a 'hyperreactivity to environmental stimuli' or 'hyperarousal' [6,10,14]. Wade and Mater concluded that the Morris maze task may have interacted with the exaggerated arousability of the rats, and the subsequent level of arousal was detrimental to learning.…”
Section: Discussionmentioning
confidence: 99%
“…This test also shows that even though both housing conditions can affect the performance of animals with brain lesions, the effects of each housing condition possibly do not rely on the same principle. The effect of enrichment is often supposed to rely on an enhancement of the adaptive capacity of the animals [9] which could help the animals with a lesion to switch more easily to alternative search strategies [34], but whereas the effect of impoverishment, though not fully understood, may rely on a difference in arousability, a different reaction to stress or a higher reactivity to cues [6,10,14]. However, it is not clear from the present data whether the impoverished rats may have also used the alternative search strategy mentioned in the enrichment study, since the search pattern of the animals has not been studied in greater detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation